The Role of Zimbabwean Museums in Creating National Identity during Post-Colonial Era: A case Study of Zimbabwe Military Museum - Nelson Jagero; Walter K. T. Chisedzi; Nevermore Sithole; Shadreck Simbarashe Chitima (Knowledge Words Publications, 2023)
The study evaluated the role of Zimbabwe Military Museum’s (ZMM) exhibitions in the creation and portrayal of national identity during post-colonial period. The research focused mainly on the museum’s collections, themes, events, interpretation and presentation of exhibitions in portraying Zimbabwe’s identity after independence up to present. This was done on the basis that most of the displays at ZMM pursue colonial ideologies whilst at the same time undermine African identity. The researchers used a qualitative research approach; the data collection methods and instruments included interviews, focus group discussions and desktop survey. This was performed in order to obtain ample information and testimonial evidence concerning audiences’ perceptions of the Zimbabwe Military Museum’s programs in relation to national identity.